2015
DOI: 10.1007/s10554-015-0680-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular volume fraction in coronary chronic total occlusion patients

Abstract: (1) To assess extracellular volume fraction (ECV) and regional systolic function in patients presenting with coronary chronic total occlusion (CTO) in areas without significant late gadolinium enhancement (LGE), and (2) to investigate the correlation between angiography collateral flow and ECV in territories supplied by CTO vessels. A total of 50 angiographically documented CTO patients and 15 age- and sex-matched normal controls were recruited to the study. Myocardial ECV, was calculated in infarcted, global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The presence of well-developed collateral circulation plays a protective role in the downstream myocardium assigned to CTO vessels. Our previous study showed, as it already has been demonstrated by Chen et al (6), Choi et al (7), and Zhang et al (28), that well-developed collaterals were associated with a lower incidence of MI, lower transmurality of LGE and LGE volume, and reduced regional wall motion abnormality score. Studies to date have mainly focused on the relationship between collateral circulation and baseline CMR markers.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The presence of well-developed collateral circulation plays a protective role in the downstream myocardium assigned to CTO vessels. Our previous study showed, as it already has been demonstrated by Chen et al (6), Choi et al (7), and Zhang et al (28), that well-developed collaterals were associated with a lower incidence of MI, lower transmurality of LGE and LGE volume, and reduced regional wall motion abnormality score. Studies to date have mainly focused on the relationship between collateral circulation and baseline CMR markers.…”
Section: Discussionsupporting
confidence: 76%
“…Successful CTO percutaneous coronary intervention (PCI) leads to angina relief, lower mortality, as well as improvement of left ventricular (LV) function (345). In the setting of CTO with chronic myocardial ischemia, the affected myocardium shows depressed contractility to compensate the insult, while the collateral circulation improves blood supply to areas of downstream myocardium, and is closely associated with regional wall motion (67). However, whether the collateral circulation plays a role in the prediction of functional recovery in CTO patients has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary MrA was found to correlate well with stressperfusion MRI for detecting significant CAD and helps exclude CAD in asymptomatic individuals [28]. extracellular volume (eCv) in patients with chronic total coronary artery occlusion was found to be increased beyond that observed with late gadolinium enhancement (lGe), and correlated with the lv regional wall motion abnormality, which appears to reflect diffuse myocardial fibrosis [29]. A comparison of semi-automated scar quantification techniques using high-resolution, 3-dimensional late-gadolinium enhancement magnetic resonance imaging was examined by rajchl et al [30].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 90%
“…Moreover, ECV is independent of field strength, remains constant or increases slightly over time after a simple bolus, and is more reproducible across MR scans, which may facilitate quantitative assessment in comparison with an isolated T1 measurement. To date, only limited data are available concerning application of myocardial T1‐mapping in chronic total occlusion (CTO) patients. In this study, we aimed to determine whether myocardial ECV could serve as a biomarker for assessing the severity of myocardial injury, angiographic collateral flow and regional functional recovery after revascularizaion.…”
mentioning
confidence: 99%